Model predictive control applied to A 2-DOF helicopter. - Oliveira Júnior, José Genario de (2018)
This work presents an embedded model predictive control application to a 2-DOF Helicopter Process. The mathematical modeling of the plant is first presented along with an analysis of the linear model. Then, the incremental state-space representations used in the MPC formulation are derived. The MPC technique is then defined, along with how to rewrite the physical constraints into the problem formulation. After that, a discussion on the utilized Quadratic Programming solver is presented along with possible alternatives to it, showing some considerations on which matrices to calculate beforehand for an embedded application. Finally, system identification is performed and the experimental results are presented.